Factors associated with failure of exclusive breastfeeding practice - Desy Purnamasari; Mufdlilah Mufdlilah (Journal of Health Technology Assessment in Midwifery, 2018)
Failure of exclusive breastfeeding has become a significant issue in Indonesia. There are several factors lead to such issue occurred. This cross-sectional analytical survey study aimed to investigate the relationship of mother's knowledge, mother's education and mother's job to unsuccessful exclusive breastfeeding. There were 31 mothers with infants aged 0-24 months participated in this study. Data were collected by employing closed-ended questionnaire and analyzed by applying chi-square test. The results revealed that knowledge, maternal education and maternal job associated with unsuccessful breastfeeding (p 0.05). The failure of exclusive breastfeeding were influenced by mothers’ knowledge, mothers’ education and mothers’ occupation.